2021
DOI: 10.3390/healthcare9101313
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cerebral Infarction Risk and Medication Adherence in Atrial Fibrillation Patients Taking Direct Oral Anticoagulants

Abstract: Direct oral anticoagulants (DOACs) are available for nonvalvular atrial fibrillation patients. The advantage of DOACs is that regular anticoagulation monitoring is not required. However, adherence to the recommended regimen is essential. We investigated the association between medication adherence and the risk of cerebral infarction in patients taking DOACs. Patients admitted to any of the participating hospitals for cerebral infarction from September 2018 to February 2020 and prescribed DOACs before admission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“… 5 Real‐world data also demonstrate that poor adherence to DOACs results in decreased efficacy and increased risk of adverse events. 6 , 7 These observations support the need for centralized management of patients on DOACs. An Anticoagulation Management Service (AMS) providing DOAC services can optimize anticoagulation therapy during transitions of care, where many opportunities for medication errors arise.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“… 5 Real‐world data also demonstrate that poor adherence to DOACs results in decreased efficacy and increased risk of adverse events. 6 , 7 These observations support the need for centralized management of patients on DOACs. An Anticoagulation Management Service (AMS) providing DOAC services can optimize anticoagulation therapy during transitions of care, where many opportunities for medication errors arise.…”
Section: Introductionmentioning
confidence: 74%
“…Inappropriate prescribing was associated with an increased risk of thromboembolic and hemorrhagic events 5 . Real‐world data also demonstrate that poor adherence to DOACs results in decreased efficacy and increased risk of adverse events 6,7 . These observations support the need for centralized management of patients on DOACs.…”
Section: Introductionmentioning
confidence: 88%
“…In light of the above data, it is essential to monitor and follow up patients with NVAF in their course of care, and this is supported by studies in the literature which show that the management of patients treated with DOACs under the supervision of pharmacists is associated with greater adherence to treatment in real life 52…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there is a 25% likelihood that patients on DOACs will undergo a surgical or interventional procedure over a period of 24 months [ 102 ].…”
Section: Af Patients Undergoing Non-cardiac Surgerymentioning
confidence: 99%
“…According to the most recent guidelines [ 102 ], if there is a need for surgery during the DOAC strategy, several factors, such as the kind of surgery and its specific bleeding risk, the patient’s characteristics, and the anticoagulation type, should be evaluated. Moreover, whether the procedure is urgent or not is crucial for patient management.…”
Section: Af Patients Undergoing Non-cardiac Surgerymentioning
confidence: 99%